Effect of Shared Values in Firms to implement Forensic Accounting: A congruence of Policy, Strategy and Implementation in firms (Journal of Informatics Education and Research, 2024)
Shared values are the standard information  given to employees to form an effective and productive environment. In every interaction of management with employees, the prime focus will be on strategies to care each other without compromising organizational interest. The shared values in n organization is how to organize the thoughts, actions and interests to align with organizational interest. The shared values play a role in reducing fraudulent activities in any firm. Corporate Fraud is a venture of its own magnitude and irresistible byproduct of an economic activity, which is an impediment for achieving corporate goal also social evil for countries progress. Corporate fraud magnitude is scaling high day by day, which demands for immediate action from corporate and government to mitigate and keep control on fraud instances.The study on the opportunities or the situations form occurring the fraudulent activities is important in controlling any sort of illegal behavior that may ruin the performance of the firm. This paper is focusing on factors to be considered to reduce fraudulent activities. Auditing and proper documentation may help to reduce fraudulent cases except the management driven frauds.